An M8C5 type carbon-based electronic compound, its preparation method and application
Patent Information
- Application Number
- CN202611197524.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]1、材料体系与化学计量比单一
与现有技术(如X2C型碳基电子化合物或通过单一工艺制备的相关材料)相比,本发明提供的M8C5型碳基电子化合物及其制备工艺在材料性能、结构稳定性及合成通用性方面取得了显著的进步,具体体现在以下几个方面:
Smart Images

Figure CN122897686A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electronic compound technology, specifically an M8C5 type carbon-based electronic compound, its preparation method, and its application. Background Technology
[0002] With the rapid development of the new energy field, the demand for functional materials is increasing. Among them, electrides, as functional materials with unique electronic structures, have become a research hotspot in materials science. Their core characteristic lies in the fact that electrons distributed in interstitial positions act as anions in the system, playing a role in maintaining the charge balance. This special structure endows electrides with excellent properties such as low work function and high electron density, making them promising for applications in ammonia synthesis, organocatalysis, electron emitters, and batteries. With in-depth research, various types of electrides have been developed, such as magnetic electrides, topological electrides, intermetallic electrides, and electron-deficient electrides. Among these, carbon-based electrides, possessing both the structural characteristics of carbides and the excellent characteristics of electrides, show outstanding research prospects in magnetic, superconducting, and topological applications.
[0003] However, existing carbon-based electronic compounds have two prominent problems. First, their structural types are limited. Currently known carbon-based electronic compounds have X2C stoichiometry (X = Dy, Er, Y, Sc, Gd, etc.), and these materials were mainly discovered around 2014 (Physical Review X, 2014, 4 (3), 031023). Some carbon-based electronic compounds are also superconducting electronic compounds such as Na6C and Li6C. The research system related to carbon-based electronic compounds is still mainly focused on the above-mentioned materials, and the development of new material systems is slow, so the available material systems for research are still very limited. Second, their material stability is poor. Existing carbon-based electronic compounds are easily oxidized in air, and their instability is insufficient, which seriously limits their practical applications (Advanced Materials, 2025, 37(7), 2412956).
[0004] Therefore, developing carbon-based electronic compounds with new stoichiometry and high stability has significant scientific and application value.
[0005] In addition, Hwang et al. proposed two-dimensional [Re2C] in Advanced Materials (37(7), 2412956) in 2025. 2+• 2e⁻ type carbon-based electron compounds (Re = Er, Ho, Dy, Tb), this technical solution is also the closest prior art to this invention. This technology, by designing confined interstitial quasi-atomic electrons (IQEs) in a positively charged cavity, is the first to achieve [Re₂C]... 2+ The ·2e⁻ system achieved permanent magnetism driven by interstitial electron spin lattice, laying the foundation for the application of carbon-based electronic compounds in the field of magnetic materials. This system was synthesized using an arc melting combined with high-temperature annealing. In its crystal structure, anion electrons are localized in interstitial positions within a layered Re-Re framework, exhibiting typical characteristics of electronic compounds. Although this technique represents a significant breakthrough in the structural design of carbon-based electronic compounds, it still suffers from the following significant drawbacks, primarily stemming from limitations in the compatibility between material stoichiometry and the preparation process:
[0006] 1. The material system and stoichiometry are limited. This existing technology only discloses [Re₂C] composed of four heavy rare earth elements: Re = Er, Ho, Dy, and Tb. 2+ The 2e⁻ type (i.e., Re:C=2:1) stoichiometric ratio is fundamentally due to the fact that the magnetic design of this system is highly dependent on heavy rare earth elements. f The strong exchange coupling between electrons and the two-dimensional interstitial electron spin lattice strictly limits the expandable elemental range to the aforementioned heavy rare earth subset. Current technologies fail to provide a universal stoichiometric scheme for transitioning to other transition metals such as Sc, Ti, Zr, and Hf, resulting in severely insufficient elemental coverage and structural diversity in carbon-based electronic compounds.
[0007] 2. Material stability remains limited. In this existing technology, anion electrons are localized in a layered structure [Re2C]. 2+ The interlayer gaps in the framework have a high degree of exposure. Due to the large area of direct contact between interlayer electrons and the external environment in the layered structure, this type of material is still easily oxidized in air and prone to hydrolysis in aquatic environments, resulting in insufficient stability and severely limiting its practical applications.
[0008] 3. Insufficient adaptability of the preparation process. The existing technology adopts a synthesis route of arc melting combined with high-temperature annealing. Although this route is applicable to rare earth systems, it does not provide differentiated preparation schemes for transition metals. In fact, different transition metals have significant differences in their reactivity with carbon, carbon diffusion barriers, and ordering temperature requirements—arc melting cannot simultaneously meet the requirements for efficient synthesis of all transition metal elements, resulting in slow progress in the development of new material systems.
[0009] In summary, the closest existing technologies mainly rely on limiting the rare earth element subset and a single [Re2C] element. 2+The 2e⁻ stoichiometry was used to achieve the magnetic design of carbon-based electronic compounds, but it failed to address the shortcomings of carbon-based electronic compounds in terms of element coverage, structural diversity, air and water stability, and the universality of preparation processes. Summary of the Invention
[0010] To address the shortcomings of the existing technologies, this invention provides an M8C5-type carbon-based electronic compound, its preparation method, and its applications. Compared with the prior art, the M8C5-type (M:C=8:5) carbon-based electronic compound of this invention is a novel electronic compound, with the transition metal M encompassing five elements: Sc, Ti, Zr, Hf, and Er. R m The [Re2C] crystal structure exhibits a maximum electron localization function (ELF) ≥ 0.7, with anion electrons localized within more enclosed cation octahedral interstices and exhibiting low exposure, thus demonstrating significantly superior performance compared to existing [Re2C] crystals. 2+ • The air and water stability of the 2e⁻ type material. Furthermore, this invention provides two preparation processes: sintering reaction and electric arc melting. Both methods can be used to synthesize all M8C5 materials, and the choice can be flexible based on the reaction characteristics of different transition metals with carbon. This invention achieves significant breakthroughs in three dimensions: material system, stability, and preparation flexibility.
[0011] Based on the above technical objectives, the present invention adopts the following technical solution: This invention protects an M8C5 type carbon-based electronic compound, wherein M in the M8C5 type carbon-based electronic compound is selected from one of Sc, Ti, Zr, Hf, Er, and the stoichiometric ratio M:C = 8:5.
[0012] Preferably, the M8C5 type carbon-based electronic compound has R m In this type of crystal structure, the electrons of the anions are localized in the more closed octahedral interstices, becoming 0-dimensional electronic compounds. This fundamentally reduces the exposure of interstitial electrons, thereby significantly improving the air and water stability of the material. Furthermore, the maximum value of the electron localization function of the localized electrons is ≥0.7. 0.7 is used as a threshold to confirm the electronic compound. Systems below 0.7 (such as 0.6) are usually ordinary metallic bonds or weak localization.
[0013] This invention also protects a method for preparing M8C5 type carbon-based electronic compounds, which are prepared by sintering reaction or electric arc melting.
[0014] Preferably, the sintering reaction method includes the following steps: mixing transition metal M powder with a carbon source and sintering in an inert atmosphere; wherein the transition metal M powder is selected from one of Sc powder, Ti powder, Zr powder, Hf powder, and Er powder.
[0015] Preferably, the sintering conditions are: first, hold at 1400℃~1500℃ for 4h~12h, and then hold at 1550℃~1800℃ for 3h~5h.
[0016] Preferably, the electric arc melting method includes the following steps: mixing transition metal M powder with a carbon source, first melting to obtain an ingot, then tightly wrapping the ingot with high-purity tantalum foil, and then annealing; wherein, the transition metal M powder is selected from one of Sc powder, Ti powder, Zr powder, Hf powder, and Er powder.
[0017] Preferably, the annealing conditions are: holding at 1000℃~1500℃ for 5 to 7 days.
[0018] Preferably, the molar ratio of transition metal M powder to carbon source is 8:5.25~5.5.
[0019] Preferably, the carbon source is selected from one of graphite powder, semi-coke, carbon black, activated carbon, and coke powder.
[0020] This invention also protects the application of the above-mentioned M8C5 type carbon-based electronic compound in the preparation of ammonia synthesis catalysts.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: Compared with existing technologies (such as X2C-type carbon-based electronic compounds or related materials prepared by a single process), the M8C5-type carbon-based electronic compound and its preparation process provided by this invention have achieved significant progress in terms of material properties, structural stability, and synthetic versatility, specifically in the following aspects: 1. Structural Novelty and Superior Performance: This invention successfully overcomes the stoichiometric limitations of existing carbon-based electronic compounds of the X2C and M6C types, constructing a novel M8C5 type (M:C = 8:5) crystal structure. By precisely controlling the metal-carbon ratio and reaction conditions, carbon atoms are encouraged to enter the octahedral interstitial spaces of the transition metal lattice, forming a close-packed arrangement different from the traditional layered structure. This optimized spatial configuration allows the anion electrons inside the M8C5 type carbon-based electronic compound to be localized in more enclosed polyhedral centers, significantly reducing electron exposure. Theoretical calculations and experimental characterization both confirm that this structure effectively improves the stability of interstitial electrons, providing a fundamental structural solution to the problem of poor stability commonly found in carbon-based electronic compounds.
[0022] 2. Excellent Chemical Stability: Thanks to the deep localization of anion electrons, the M8C5 carbon-based electronic compound of this invention exhibits unprecedented air and water stability. Unlike existing X2C type materials which readily oxidize and discolor in air, the M8C5 carbon-based electronic compound of this invention maintains its intact crystal structure even after prolonged exposure to air or immersion in water, without significant oxidation or hydrolysis. This characteristic greatly expands the practical application boundaries of carbon-based electronic compounds.
[0023] It should be noted that the five M8C5-type carbon-based electronic compounds of this invention exhibit certain differences in stability. Among them, Ti8C5, Zr8C5, and Hf8C5 show particularly outstanding performance. Therefore, in the stability comparison experiment, we selected these three materials and conducted systematic air stability and water stability comparison tests with the existing X2C-type representative material Y2C.
[0024] 3. High Flexibility and Versatility of Preparation Processes: Addressing the differences in physicochemical properties among transition metal elements, this invention innovatively provides two parallel and universal preparation routes: sintering reaction and electric arc melting. The sintering reaction method utilizes solid-state diffusion kinetics, making it particularly suitable for processing highly reactive metal systems. It boasts advantages such as simple process, strong raw material adaptability, and ease of large-scale production. The electric arc melting method, with its high energy density and rapid cooling characteristics, can efficiently promote in-situ reactions and atomic rearrangements between metals and carbon, resulting in products that typically exhibit high density and purity.
[0025] Both methods can independently and efficiently synthesize M8C5-type carbon-based electronic compounds covering the entire elemental spectrum. This "dual-track parallel" strategy endows the invention with strong versatility, allowing researchers to freely choose the most suitable process route based on laboratory conditions or the actual needs of industrial production, completely breaking the previous constraints of a single synthetic route on the expansion of carbon-based electronic compound systems.
[0026] 4. Potential Economic and Social Benefits: This invention exhibits good raw material compatibility during preparation. For example, industrial byproducts such as semi-coke powder can be directly used as carbon sources. This not only reduces raw material costs but also achieves high-value utilization of coal chemical waste, aligning with the development concept of green chemistry. Furthermore, the highly stable M8C5 type carbon-based electronic compound has broad application prospects in electron emission devices, special catalysis, and energy storage, and is expected to generate significant economic benefits. Attached Figure Description
[0027] Figure 1 This is a flowchart illustrating the screening and design process for the M8C5 type carbon-based electronic compounds of this invention.
[0028] Figure 2 Phonon spectra of Sc8C5 in Example 1, Ti8C5 in Example 2, Zr8C5 in Example 5, Hf8C5 in Example 7, and Er8C5 in Example 9.
[0029] Figure 3 In the figure, (a) is a crystal structure diagram of Sc8C5 in Example 4, and (b) is a projected energy band diagram of local electrons of Sc8C5 in Example 4.
[0030] Figure 4 In the figure, (a) is a crystal structure diagram of Ti8C5 in Example 3, and (b) is a projected energy band diagram of local electrons of Ti8C5 in Example 3.
[0031] Figure 5 In the figure, (a) is a crystal structure diagram of Zr8C5 in Example 6, and (b) is a projected band diagram of local electrons of Zr8C5 in Example 6.
[0032] Figure 6 In the figure, (a) is a crystal structure diagram of Hf8C5 in Example 8, and (b) is a projected energy band diagram of local electrons of Hf8C5 in Example 8.
[0033] Figure 7 In the figure, (a) is a crystal structure diagram of Er8C5 in Example 10, and (b) is a projected band diagram of local electrons of Er8C5 in Example 10.
[0034] Figure 8 The image shows the XRD pattern of Sc8C5 from Example 1.
[0035] Figure 9 The image shows the XRD pattern of Ti8C5 in Example 2.
[0036] Figure 10 The image shows the XRD pattern of Zr8C5 in Example 5.
[0037] Figure 11 The image shows the XRD pattern of Hf8C5 in Example 7.
[0038] Figure 12 The image shows the XRD pattern of Er8C5 in Example 9.
[0039] Figure 13 The chart shows a comparison of the air stability of Ti8C5 from Example 2, Zr8C5 from Example 5, Hf8C5 from Example 7, and Y2C from Comparative Example 1.
[0040] Figure 14 The graph shows a comparison of the water stability of Ti8C5 from Example 2, Zr8C5 from Example 5, Hf8C5 from Example 7, and Y2C from Comparative Example 1.
[0041] Figure 15 The graph shows a comparison of the ammonia synthesis performance of Sc8C5 from Example 1, Ti8C5 from Example 2, Zr8C5 from Example 5, Hf8C5 from Example 7, Er8C5 from Example 9, and Y2C from Comparative Example 1. Detailed Implementation
[0042] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below with reference to specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the present invention. Unless otherwise specified, the experimental methods and detection methods described in the following embodiments are conventional methods; unless otherwise specified, the reagents and materials described are commercially available.
[0043] Based on the analysis of background technology and existing solutions, this invention aims to overcome the core bottleneck in existing carbon-based electronic compound technology, namely, the lack of structural diversity, poor stability and limited adaptability of preparation process caused by the single stoichiometry of the material system.
[0044] Although existing research has explored the design of [Re2C] 2+ • 2e⁻ type (Re=Er, Ho, Dy, Tb) carbon-based electronic compounds have achieved a significant breakthrough in the field of permanent magnetism. This approach still relies entirely on rare earth elements for performance breakthroughs. f The strong exchange coupling between electrons and interstitial quasi-atomic electrons has not been actively expanded to broaden the stoichiometric diversity and elemental coverage of carbon-based electronic compounds. This results in the following unresolved technical problems:
[0045] 1. Limited Structural Types Restrict Material System Expansion: Existing carbon-based electronic compounds are mainly concentrated in X2C and M6C stoichiometric systems. The fundamental reason is that current approaches rely heavily on the physicochemical properties of specific electronic configurations or subsets of elements, failing to establish a universal stoichiometric framework applicable to a wider range of transition metals. This has long confined the studyable systems of carbon-based electronic compounds to a few materials, severely limiting further development in this field.
[0046] 2. Insufficient material stability restricts practical applications: In existing carbon-based electronic compounds, anion electrons are localized in the interlayer gaps of the layered structure, with a high degree of exposure. Due to the large interlayer spacing of the M and M layers in the layered structure, the interlayer electrons have a large direct contact area with the external environment, which makes such materials easily oxidized in air and prone to hydrolysis in water. This stability defect stems from the design limitations of the crystal structure itself, rather than being solved by simple surface modification.
[0047] 3. Insufficient compatibility between preparation process and material system: Existing technologies mainly rely on a single electric arc melting method to synthesize carbon-based electronic compounds. Although this method is applicable to some rare earth element systems, there are significant differences in the reactivity of different transition metals with carbon, carbon diffusion barriers, and ordering temperature requirements. A single process route cannot simultaneously meet the high-efficiency synthesis requirements of the entire series of transition metal elements.
[0048] Therefore, the objective of this invention is to overcome the limitation of existing carbon-based electronic compounds in terms of stoichiometry and provide a new class of carbon-based electronic compounds with a novel stoichiometric ratio (M8C5, M:C=8:5). Specifically, this is achieved through the design of... R m The novel crystal structure localizes anion electrons within more enclosed octahedral interstices, creating a zero-dimensional electron compound. This fundamentally reduces the exposure of interstitial electrons, significantly improving the material's air and water stability. Furthermore, this invention provides two preparation processes: sintering reaction and arc melting. Both methods can be used to synthesize all M8C5 materials (M = Sc, Ti, Zr, Hf, Er). The choice of method depends on the reaction characteristics of different transition metals with carbon, eliminating the need for specific process routes for different elements. Ultimately, this promotes the development of carbon-based electron compounds towards higher structural diversity, higher stability, and greater preparation flexibility.
[0049] The M8C5 type carbon-based electronic compounds of this invention were obtained through a combination of systematic theoretical screening and experimental verification. For example... Figure 1 As shown, firstly, based on first-principles density functional theory (DFT) calculations, this study performed high-throughput screening on candidate structures composed of various transition metals and carbon, obtaining a novel M8C5 type. R m Carbon-based electronic compounds in space groups are then determined based on thermodynamic and kinetic stability:
[0050] Table 1. E-values of carbon-based electronic compounds hull Value table (1) Thermodynamic stability: The convex hull energy (E) of each candidate structure relative to a known stable phase is calculated. hull To evaluate. When E hull A value of 0 meV / atom indicates that the compound is thermodynamically stable. The calculation results are shown in Table 1, with E values for Ti8C5, Zr8C5, and Hf8C5... hull Both Sc8C5 and Er8C5 have an E value of 0 meV / atom, indicating a thermodynamically stable state; hullThe values are 15 meV / atom and 44 meV / atom, respectively, indicating a metastable state but still feasible for experimental synthesis. In contrast, the Eatom values of the M8C5 structure formed by other transition metals (such as La, Ce, Pr, Sm, Gd, Tb, Dy, Ho, and Y) are significantly higher. hull The values are generally high (>50 meV / atom), indicating insufficient thermodynamic stability, and therefore they were excluded.
[0051] (2) Kinetic stability: Phonon spectrum calculations are performed on thermodynamically feasible candidate materials. For example... Figure 2 As shown, the results indicate that the phonon spectra of Ti8C5, Zr8C5, Hf8C5, Sc8C5, and Er8C5 do not exhibit imaginary frequencies throughout the Brillouin zone, demonstrating their dynamic stability and suggesting that they can be theoretically synthesized experimentally.
[0052] Based on the theoretical screening and preliminary experimental synthesis attempts described above, this study ultimately identified five transition metals—Sc, Ti, Zr, Hf, and Er—as target elements, and conducted comprehensive experimental synthesis verification of these five M8C5 compounds. Experimental results confirmed that all five materials could be successfully prepared via sintering reaction or arc melting, and the products exhibited high purity, high crystallinity, and excellent stability. This closed-loop process of "theoretical screening—experimental verification" ensures the scientific rigor and reproducibility of this invention.
[0053] This invention provides an M8C5-type carbon-based electronic compound, aiming to overcome the technical bottlenecks of existing carbon-based electronic compounds, such as their simple structure, poor stability, and limited preparation processes. The core of this invention lies in the design of a novel stoichiometric ratio (M:C=8:5) and... R m The crystal structure is characterized by localizing anion electrons within closed octahedral interstices, thereby significantly enhancing stability. Furthermore, this invention provides two preparation processes: a sintering reaction method and an electric arc melting method. Both methods can be used to synthesize all target materials, offering high process flexibility.
[0054] Composition of the technical solution and the relationship between its components: The general chemical formula of the carbon-based electronic compound of this invention is M8C5, wherein the transition metal M is Sc, Ti, Zr, Hf, or Er, and the carbon-based electronic compound has... R m It has a crystal structure with a maximum electron localization function (ELF) of ≥0.7 for local electrons and the projected energy bands of local electrons in the band structure are located in the range of -1eV to 0eV near the Fermi level.
[0055] To achieve controllable preparation of the above materials, the present invention provides two process routes, the constituent elements and their synergistic relationships of which are as follows: (1) Sintering reaction method system: This method is applicable to all M elements, and its system contains the following core components: Raw material composition ratio: Transition metal M powder (purity ≥99.9%) and carbon source (graphite powder or high-purity semi-coke powder) are accurately weighed and mixed in a molar ratio of M:C=8:5. Considering the volatilization loss in the actual reaction, the actual amount of carbon source is 1.05 to 1.1 times the theoretical amount.
[0056] Reaction apparatus: Horizontal high-temperature tube furnace, equipped with a high-purity argon (Ar) atmosphere control system.
[0057] Process parameter relationship: A two-stage heating strategy is adopted. The first stage heating rate is 1℃ / min~5℃ / min, the target temperature is 1400℃~1500℃, and the holding time is 4h~12h to allow the raw material to fully diffuse into the solid phase; then the temperature is increased to 1550℃~1800℃ at 1℃ / min~5℃ / min and held for 3h~5h to complete the formation and ordering of the carbide phase.
[0058] The relationship between the three is as follows: the proportion of raw materials is the basis for determining the final stoichiometric ratio; the tube furnace provides a uniform high-temperature field; and the segmented temperature control process precisely controls the dissolution and precipitation kinetics of carbon in the metal phase, avoiding the formation of impurity phases of single-phase carbides.
[0059] (2) Electric arc melting system: This method is also applicable to all M elements to obtain highly crystalline products. Its system contains the following core components:
[0060] Raw material composition ratio: Transition metal M block or M powder (purity ≥99.9%) and carbon source (high purity graphite powder or semi-coke) are accurately weighed and mixed in a molar ratio of M:C=8:5. Considering the volatilization loss in the actual reaction, the actual amount of carbon source is 1.05 to 1.1 times the theoretical amount.
[0061] Reaction apparatus: Non-consumable vacuum arc melting furnace, equipped with a high-purity argon gas protection system and quartz tube annealing accessories.
[0062] Process parameter relationship: First, under a high-purity argon atmosphere, multiple (≥3 times) electric arc melting is carried out at 0.05MPa~0.1MPa and 30A~100A. The electric arc is sufficient to melt the transition metal M block or M powder and the carbon source to ensure that the raw materials initially become electronic compounds. Then, the resulting ingot is tightly wrapped with high-purity tantalum foil, sealed in a vacuum-sealed quartz tube, and heated to 1000℃~1500℃ at a rate of 1℃ / min~5℃ / min, and held at that temperature for 5~7 days for annealing treatment.
[0063] The relationship between the three is as follows: electric arc melting provides instantaneous high temperature to achieve rapid homogenization of elements; tantalum foil wrapping effectively isolates the ingot from the quartz tube at high temperature and prevents impurities from penetrating; long-term annealing provides sufficient kinetic time for atomic rearrangement, which further improves the purity of carbon-based electronic compounds.
[0064] It should be noted that the core innovation of the M8C5 type carbon-based electronic compound of this invention lies in its unique R m Type II crystal structure and the resulting electronic localization properties (ELF) max ≥0.7). Therefore, any structure based on the M8C5 structure of this invention, where the M site is partially replaced by a small amount of other transition metals or rare earth elements (such as Y, La, Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Yb, Lu, etc.), while still maintaining... R m Materials with the same crystal structure and electronic compound properties fall within the scope of protection of this invention. This is because the substitution of small amounts of elements does not change the basic crystal framework and interstitial electron localization mechanism of M8C5, and its technical essence is the same as that of this invention. Similarly, introducing small amounts of non-metallic elements into carbon sites for doping, as long as it does not damage the M8C5 crystal structure and electronic compound properties, will not change the basic crystal framework and interstitial electron localization mechanism of M8C5. R m Type principal phase structure and ELF max An electronic local characteristic of ≥0.7 should also be considered an equivalent embodiment of the present invention.
[0065] This invention successfully yielded a class of carbon-based electronic compounds with novel stoichiometric ratios and demonstrated their excellent air and water stability. This technical solution overcomes the limitations of existing X₂C single-structure compounds. Furthermore, this invention provides two preparation processes: sintering reaction and arc melting, laying the foundation for the practical application of carbon-based electronic compounds. Finally, the materials studied are applied in the field of ammonia synthesis catalysis.
[0066] The technical solution of the present invention will be studied below using examples and comparative examples. The specific research methods and results are shown below: Example 1 The preparation method of Sc8C5 carbon-based electronic compounds, in this embodiment, adopts the electric arc melting method, and includes the following steps: Step S1, Raw material loading: Weigh high-purity scandium metal blocks and high-purity graphite powder according to the stoichiometric ratio of Sc:C=8:5. The graphite powder is pressed into shape by a powder press. In order to improve the melting efficiency and ensure a sufficient supply of carbon elements, 3% graphite is added in excess during actual operation. The raw materials are loaded into a high-purity copper crucible with a groove at the bottom.
[0067] Step S2, Arc Melting Process: Place the copper crucible in a non-consumable vacuum arc melting furnace, and evacuate the entire apparatus to ≤10°C. -3 After Pa, high-purity argon gas is introduced as a protective atmosphere, and the pressure is maintained at 0.1 MPa. The power supply is turned on, and under 50A conditions, the high temperature generated by the high-voltage arc is used to completely melt the Sc and C raw materials. In order to ensure uniform composition and eliminate macroscopic segregation, at least three repeated melting processes are required under electromagnetic stirring or manual turning conditions, and finally a metal ingot with a silver-gray surface is obtained.
[0068] Step S3, Annealing treatment (quality improvement process): The metal ingot obtained by electric arc melting is tightly wrapped with high-purity tantalum foil to isolate it from oxygen and moisture in the air, and then sealed in a quartz tube in an inert gas atmosphere for annealing.
[0069] Clarification: This annealing step is intended for further purification. At high temperatures, the tantalum foil will adsorb residual oxygen impurities. At the same time, long-term annealing helps the microcrystal rearrangement generated during the melt condensation process, thereby improving the macroscopic crystallinity.
[0070] Annealing process parameters: Heat to 1200℃ at a rate of 3℃ / min, hold for 7 days, and then cool to room temperature with the furnace after the holding period.
[0071] Step S4, Post-processing: Open the quartz tube and remove the metal ingot wrapped with tantalum foil. Remove the tantalum foil and oxide scale from the surface, and then prepare the Sc8C5 carbon-based electronic compound of the required size by mechanical ball milling.
[0072] Example 2 The preparation method of Ti8C5 carbon-based electronic compounds is described in this embodiment using the electric arc melting method. The preparation steps are the same as in Example 1, except that in the electric arc melting method, the temperature is increased to 1000℃ at a rate of 3℃ / min, held for 7 days, and then cooled to room temperature with the furnace after the holding period.
[0073] Example 3 The preparation method of Ti8C5 carbon-based electronic compounds, in this embodiment, adopts a sintering reaction method, including the following steps: Step S1, Raw material preparation and mixing: According to the stoichiometric ratio of the target product Ti8C5 (Ti:C=8:5), accurately weigh high-purity titanium powder and graphite powder. To ensure uniform mixing, place the weighed powder in an agate mortar and grind it in a nitrogen-protected glove box for 45 minutes until a uniform black paste-like mixture is obtained.
[0074] Step S2, Compression Molding: Transfer the black paste mixture into a stainless steel mold and compress it on a powder tablet press. Apply a pressure of 10 MPa and hold the pressure for 5 minutes to obtain a round blank with a diameter of 10 mm.
[0075] Step S3, Two-stage high-temperature sintering: The pressed green body is encapsulated in a high-purity carbon tube and placed in a tube furnace. To ensure sufficient diffusion of the carbon source and phase purity, a two-stage heating process is adopted: First stage of heat preservation: The temperature is increased to 1500℃ at a rate of 3℃ / min and held for 5 hours to allow the raw materials to be initially alloyed and release volatiles.
[0076] Second stage of heat preservation: Continue to heat to 1550℃ at a rate of 3℃ / min and hold for 2 hours to promote the full diffusion of Ti and C atoms and complete the formation of Ti8C5 phase.
[0077] Step S4, Post-processing: After the furnace temperature naturally cools to room temperature, Ti8C5 carbon-based electronic compound bulk material is obtained, which is then ground to obtain Ti8C5 carbon-based electronic compound powder.
[0078] Example 4 The preparation method of Sc8C5 carbon-based electronic compounds in this embodiment adopts the sintering reaction method, which is the same as the preparation steps in Example 3. The only difference is that in the sintering reaction, the temperature is first raised to 1500℃ at a rate of 3℃ / min and held for 6h; then the temperature is raised to 1600℃ at a rate of 3℃ / min and held for 2h.
[0079] Example 5 The preparation method of Zr8C5 carbon-based electronic compounds is described in this embodiment using the electric arc melting method. The preparation steps are the same as in Example 1, except that in the electric arc melting method, the temperature is increased to 1100℃ at a rate of 1℃ / min, held for 7 days, and then cooled to room temperature with the furnace after the holding period.
[0080] Example 6 The preparation method of Zr8C5 carbon-based electronic compounds in this embodiment adopts the sintering reaction method, which is the same as the preparation steps in Example 3. The only difference is that in the sintering reaction, the temperature is first raised to 1400℃ at a rate of 1℃ / min and held for 6h; then the temperature is raised to 1600℃ at a rate of 1℃ / min and held for 2h.
[0081] Example 7 The preparation method of Hf8C5 carbon-based electronic compound is as follows: the preparation steps are the same as those in Example 1, except that in the electric arc melting method, the temperature is raised to 1200°C at a rate of 5°C / min, held for 7 days, and then cooled to room temperature with the furnace after the holding period.
[0082] Example 8 The preparation method of Hf8C5 carbon-based electronic compounds in this embodiment adopts the sintering reaction method, which is the same as the preparation steps in Example 3. The only difference is that in the sintering reaction, the temperature is first raised to 1500℃ at a rate of 5℃ / min and held for 5h; then the temperature is raised to 1650℃ at a rate of 5℃ / min and held for 5h.
[0083] Example 9 The preparation method of Er8C5 carbon-based electronic compound in this embodiment is the same as that in Example 1, which is the same as the preparation steps. The only difference is that in the electric arc melting method, the temperature is raised to 1200°C at a rate of 2°C / min and held for 7 days. After the holding period, the temperature is cooled to room temperature with the furnace.
[0084] Example 10 The preparation method of Er8C5 carbon-based electronic compounds in this embodiment adopts the sintering reaction method, which is the same as the preparation steps in Example 3. The only difference is that in the sintering reaction, the temperature is first raised to 1400℃ at a rate of 4℃ / min and held for 5h; then the temperature is raised to 1500℃ at a rate of 4℃ / min and held for 3h.
[0085] Comparative Example 1 Existing methods for preparing Y2C carbon-based electronic compounds include the following steps: Step S1, Raw material loading: Weigh high-purity yttrium metal powder and high-purity graphite powder according to the stoichiometric ratio of Y:C=2:1. The graphite powder is pressed into shape by a powder press. In order to improve the melting efficiency and ensure a sufficient supply of carbon elements, 3% graphite is added in excess during actual operation. The raw materials are loaded into a high-purity copper crucible with a groove at the bottom.
[0086] Step S2, Arc Melting Process: Place the copper crucible in a non-consumable vacuum arc melting furnace, and evacuate the entire apparatus to ≤10°C. -3 After Pa, high-purity argon gas is introduced as a protective atmosphere, and the pressure is maintained at 0.1 MPa. The power supply is turned on, and the high temperature generated by the high-voltage arc is used to completely melt the Y and C raw materials. In order to ensure uniform composition and eliminate macroscopic segregation, at least three repeated melting processes are required under electromagnetic stirring or manual turning conditions, and finally a Y2C electronic compound with a silver-gray surface is obtained.
[0087] The following studies use the M8C5 type carbon-based electronic compounds from Examples 1 to 10 and the Y2C carbon-based electronic compound from Comparative Example 1 as examples. The specific research methods and results are shown below: like Figures 3-7As shown, first-principles calculations reveal that Sc8C5, Ti8C5, Zr8C5, Hf8C5, and Er8C5 all exhibit the significant characteristics of electronic compounds. The charge localization function plot (Isosurfaces=0.7) shows the presence of electronic localization in the crystal structure, denoted by V, with the projected energy bands of the localized electrons located near the Fermi level.
[0088] like Figures 8-12 As shown, the prepared carbon-based electronic compounds Sc8C5, Ti8C5, Zr8C5, Hf8C5 and Er8C5 all have good purity and excellent crystallinity.
[0089] like Figure 13 As shown, the air stability of the carbon-based electronic compounds prepared in Examples 2, 5, and 7, and the Y2C of Comparative Example 1, was investigated. Specifically, the Ti8C5 powder prepared in Example 2, the Zr8C5 powder prepared in Example 5, the Hf8C5 powder prepared in Example 7, and the Y2C powder of Comparative Example 1 were exposed to air (temperature 25±2℃, relative humidity 50±10%), and color changes were observed. The Y2C powder began to change from black to white after about 1 minute of exposure to air, and partially turned white after about 15 minutes, indicating severe oxidation. However, the Ti8C5, Zr8C5, and Hf8C5 powders of this invention did not show significant color changes after being exposed to air for several hours or even days under the same conditions. These results demonstrate that the Ti8C5, Zr8C5, and Hf8C5 carbon-based electronic compounds of this invention exhibit superior air stability compared to existing X2C-type materials.
[0090] like Figure 14 As shown, the water stability of the carbon-based electronic compounds prepared in Examples 2, 5, and 7, and the Y2C of Comparative Example 1, was investigated. Specifically, the Ti8C5 block prepared in Example 2, the Zr8C5 block prepared in Example 5, the Hf8C5 block prepared in Example 7, and the Y2C block of Comparative Example 1 were placed in deionized water (temperature 25±2℃), and the changes in the materials were observed. The Y2C block began to generate bubbles immediately after being placed in water, and the block completely disappeared after about 30 minutes, turning the solution into a turbid liquid containing a white precipitate, indicating that a severe hydration reaction had occurred. However, the Ti8C5, Zr8C5, and Hf8C5 blocks of the present invention showed no significant changes when placed in water under the same conditions for several hours or even several days. These results demonstrate that the Ti8C5, Zr8C5, and Hf8C5 carbon-based electronic compounds of the present invention have superior water stability compared to existing X2C-type carbon-based electronic compounds.
[0091] like Figure 15 The figure shows a performance comparison of ammonia synthesis using Sc8C5 from Example 1, Ti8C5 from Example 2, Zr8C5 from Example 5, Hf8C5 from Example 7, Er8C5 from Example 9, and Y2C from Comparative Example 1. The experimental method was as follows: 0.1 g of ammonia synthesis catalyst was transferred to a quartz tube reactor and placed on a micro-fixed bed reactor. The temperature was increased to 400 °C at 10 °C / min under an H2 atmosphere with a flow rate of 30 mL / min, and pretreated at 400 °C for 2 h. Subsequently, the catalyst was subjected to a N2 atmosphere with a flow rate of 15 mL / min and an H2 atmosphere with a space velocity of 36000 mL / g. cat ·h -1 The catalyst activity was tested at 400℃ and 0.1 MPa. The test results showed that both Sc8C5 and Er8C5 ammonia synthesis catalysts exhibited high catalytic activity. The ammonia synthesis activities of Sc8C5 in Example 1, Ti8C5 in Example 2, Zr8C5 in Example 5, Hf8C5 in Example 7, Er8C5 in Example 9, and Y2C in Comparative Example 1 were 256 μmol / g, respectively. cat -1 h -1 75 μmolg cat -1 h -1 48 μmolg cat -1 h -1 68 μmolg cat -1 h -1 207 μmolg cat -1 h -1 and 21 μmolg cat -1 h -1 .
[0092] This invention aims to overcome a core bottleneck in existing carbon-based electronic compound technologies: insufficient structural diversity, poor stability, and limited adaptability to preparation processes due to the single stoichiometric ratio of carbon-based electronic compound systems. Before establishing M8C5 as the core of this invention, the research team conducted in-depth mechanistic studies and preliminary attempts to address the stability bottleneck of existing carbon-based electronic compounds (such as X2C type). Previous studies found that simple surface coating or trace elemental doping (such as introducing rare earth elements) can slow down the oxidation rate of X2C type carbon-based electronic compounds to some extent, but cannot fundamentally solve the problem of easy loss of interstitial electrons within the crystal lattice. Furthermore, the team explored process parameters for preparing Sc2C and Ti2C using only arc melting, finding that this method easily generates MC (such as TiC) impurity phases when processing highly reactive metals (such as Ti), making it difficult to achieve the target phase purity. These preliminary explorations clarified the research direction of this invention: "structure determines performance," meaning that the crystal structure must be changed rather than merely modified on the surface, and that a single process has limitations. These failed or inefficient experiences directly eliminated unreasonable R&D paths, providing a solid experimental basis and technical foundation for the invention to finally establish the innovative scheme of "M8C5 new structure" and "sintering + electric arc dual process in parallel".
[0093] Obviously, the above embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. An M8C5 type carbon-based electronic compound, characterized in that, In the M8C5 type carbon-based electronic compound, M is selected from one of Sc, Ti, Zr, Hf, and Er, and the stoichiometric ratio M:C = 8:
5.
2. The M8C5 type carbon-based electronic compound according to claim 1, characterized in that, M8C5 type carbon-based electronic compounds have R m It has a crystal structure and the maximum value of the electron localization function of local electrons is ≥0.
7.
3. A method for preparing the M8C5 type carbon-based electronic compound according to claim 1, characterized in that, M8C5 type carbon-based electronic compounds are prepared by sintering reaction or electric arc melting.
4. The method for preparing the M8C5 type carbon-based electronic compound according to claim 3, characterized in that, The sintering reaction method includes the following steps: mixing transition metal M powder with a carbon source and sintering in an inert atmosphere; Among them, the transition metal M powder is selected from one of Sc powder, Ti powder, Zr powder, Hf powder, and Er powder.
5. The method for preparing the M8C5 type carbon-based electronic compound according to claim 4, characterized in that, The sintering conditions are as follows: first, hold at 1400℃~1500℃ for 4h~12h, and then hold at 1550℃~1800℃ for 3h~5h.
6. The method for preparing the M8C5 type carbon-based electronic compound according to claim 3, characterized in that, The electric arc melting method includes the following steps: mixing transition metal M powder with a carbon source, first melting to obtain an ingot, then tightly wrapping the ingot with high-purity tantalum foil, and then annealing; Among them, the transition metal M powder is selected from one of Sc powder, Ti powder, Zr powder, Hf powder, and Er powder.
7. The method for preparing the M8C5 type carbon-based electronic compound according to claim 6, characterized in that, The annealing conditions are: holding at 1000℃~1500℃ for 5 to 7 days.
8. The method for preparing the M8C5 type carbon-based electronic compound according to claim 4 or claim 6, characterized in that, The molar ratio of transition metal M powder to carbon source is 8:5~5.
5.
9. The method for preparing the M8C5 type carbon-based electronic compound according to claim 4 or claim 6, characterized in that, The carbon source is selected from one of the following: graphite powder, semi-coke, carbon black, activated carbon, and coke powder.
10. The application of the M8C5 type carbon-based electronic compound of claim 1 in the preparation of ammonia synthesis catalyst.